2017
DOI: 10.1155/2017/8621239
|View full text |Cite
|
Sign up to set email alerts
|

Regional Attenuation Correction of Weather Radar Using a Distributed Microwave-Links Network

Abstract: The complex temporal-spatial variation of raindrop size distribution will affect the precision of precipitation quantitative estimates (QPE) produced from radar data, making it difficult to correct echo attenuation. Given the fact that microwave links can obtain the total path attenuation accurately, we introduce the concept of regional attenuation correction using a multiple-microwave-links network based on the tomographic reconstruction of attenuation coefficients. Derived from the radar-based equation, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…The results show that the method is effective in recovering the reflectivity information, especially under heavy rainfall conditions. More studies focused on radar attenuation correction using CMLs can be found in [134][135][136][137]. In addition, Cummings et al [138] proposed a mean-field bias adjustment method for a radar QPE based on CMLs, with similar results to a rain gauge-based adjusted QPE.…”
Section: Cooperation With Dedicated Rain Sensorsmentioning
confidence: 99%
“…The results show that the method is effective in recovering the reflectivity information, especially under heavy rainfall conditions. More studies focused on radar attenuation correction using CMLs can be found in [134][135][136][137]. In addition, Cummings et al [138] proposed a mean-field bias adjustment method for a radar QPE based on CMLs, with similar results to a rain gauge-based adjusted QPE.…”
Section: Cooperation With Dedicated Rain Sensorsmentioning
confidence: 99%
“…The measurement for oceanic precipitation is one of the basic elements of marine meteorological observation, which is significant to the study of marine weather and climate change, water, and energy cycle system as well as numerical weather forecast [1][2][3]. Rainfall measurement can be obtained directly by rain gauge [4,5] and can also be indirectly estimated by weather radar [6] and retrieved by satellite remote sensing [7] and microwave link attenuation [8,9]. Compared with radar estimation, satellite remote sensing, and microwave link attenuation retrieval of rainfall, the accuracy of rainfall measured by rain gauge is the highest and is usually used as a comparison benchmark for evaluating other precipitation measurement methods [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Atenuasi sinyal merupakan fungsi dari panjang gelombang dimana radar dengan panjang gelombang yang lebih pendek akan mengalami atenuasi yang signifikan [14]. Peristiwa hujan melemahkan gelombang ketika gelombang tersebut bertemu dengan tetes hujan [15].…”
unclassified